Functional characterization of MEKK3 in the intestinal immune response to bacterial challenges in grass carp (Ctenopharyngodon idella) - Qu, Fufa; Zeng, Xuan; Liu, Zhenzhen; Guo, Meixing; Zhang, Xia; Cao, Shenping; Zhou, Yonghua; He, Zhimin; Tang, Jianzhou; Mao, Zhuangwen; Yang, Yalin; Zhou, Zhigang; et al. (Frontiers in Immunology, 2022)
Mitogen-activated protein kinase kinase kinase 3 (MEKK3) is an evolutionarily conserved Ser/Thr protein kinase of the MEKK family that is essential for the host immune response to pathogen challenges in mammals. However, the immune function of MEKK3s in lower vertebrate species, especially in bony fish, remains largely unknown. In this study, a fish MEKK3 (designated CiMEKK3) gene was cloned and identified from grass carp (Ctenopharyngodon idella). The present CiMEKK3 cDNA encoded a 620 amino acid polypeptide containing a conserved S-TKc domain and a typical PB1 domain. Several potential immune-related transcription factor-binding sites, including activating protein 1 (AP-1), nuclear factor kappa B (NF-κB) and signal transducer and activator of downstream transcription 3 (STAT3), were observed in the 5’ upstream DNA sequence of CiMEKK3. A phylogenetic tree showed that CiMEKK3 exhibits a close evolutionary relationship with MEKK3s from Cyprinus carpio and Carassius auratus. Quantitative real-time PCR analysis revealed that CiMEKK3 transcripts were widely distributed in all selected tissues of healthy grass carp, with a relatively high levels observed in the gill, head kidney and intestine. Upon in vitro challenge with bacterial pathogens (Aeromonas hydrophila and Aeromonas veronii) and pathogen-associated molecular patterns (PAMPs) (lipopolysaccharide (LPS), peptidoglycan (PGN), L-Ala-γ-D-Glu-mDAP (Tri-DAP) and muramyl dipeptide (MDP)), the expression levels of CiMEKK3 in the intestinal cells of grass carp were shown to be significantly upregulated in a time-dependent manner. In vivo injection experiments revealed that CiMEKK3 transcripts were significantly induced by MDP challenge in the intestine; however, these effects could be inhibited by the nutritional dipeptides carnosine and Ala-Gln. Moreover, subcellular localization analysis and luciferase reporter assays indicated that CiMEKK3 could act as a cytoplasmic signal-transducing activator involved in the regulation of NF-κB and MAPK/AP-1 signaling cascades in HEK293T cells. Taken together, these findings strongly suggest that CiMEKK3 plays vital roles in the intestinal immune response to bacterial challenges, which will aid in understanding the pathogenesis of inflammatory bowel disease in bony fish.